Modeling the Spatial Pattern of Biodiversity in Secondary Grasslands: The Case of the Karst Countryside - Davidović, Danijel; Pipenbaher, Nataša; Škornik, Sonja; Ivajnšič, Danijel (Podeželje, 2026)
The study examines the course of succession and changes in species diversity of secondary grasslands in the Natura 2000 site Kras between 2014 and 2024 by integrating vegetation relevés and satellite data. The results indicate a gradual increase in aboveground biomass, confirming the process of grassland overgrowth. A spatial extrapolation model of species diversity and successional phases of the secondary grasslands studied suggests a gradual increase in the Shannon diversity index (H′), though with distinct spatial differences. A comparison of grasslands with and without interventions under the Common Agricultural Policy (CAP) revealed that the existing measures do not ensure the long-term preservation of species-rich secondary grasslands. The study highlights the importance of spatially adapted and targeted management for maintaining the conservation value and landscape diversity of the Kras.